PENENTUAN PENUMPULAN PISAU PADA PERMUKAAN KAYU - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The wear of wood cutting tools. is. generally, the process which makes a usable tool unfit for continued use. The replacement of the worn cutter by reconditioning or substitution of a new one represents a necessary cost which can be minimized by controlling tool wear. Numerous studies have been conducted through direct observations on the cutting edge using a variety of photographic methods. Such observations are quite complicated and can hardly be introduced to industrial practices. This study is aimed to explore a possibility of determining cutting tool wear indirectly through the work piece observation. It is based on assumption that knife blunting has a direct bearing on the quality of the finished product, i.e., changing the geometry of cutting marks on the wood surface.Boards of two wood species, rasamala and mangium, were seasoned to air-dry condition and planed using new sharp knives at one feed speed of 30 .m/min. Observations were carried out sequentially at 5 pianing distances, i.e., 10, 20, 40, 80 and 160 m. Cutting marks geometry on the wood surface was distinguished by rubbing the surface gently with a carbon paper. Measurements of cutting marks and the width of cutting peak were undertaken using a digital calliper. Results showed that values of cutting marks and width of catting peaks markedly increased with increasing planing distances. Blunting process was significantly affected by wood species. Knives used for planing rasamala boards blunied quicker than those used for mangium. These, to some extend, revealed a possible use of cutting marks structure on wood surface for determining the wear of cutting edge.